-3(5x+5)=5(-3x+5)

Simple and best practice solution for -3(5x+5)=5(-3x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(5x+5)=5(-3x+5) equation:



-3(5x+5)=5(-3x+5)
We move all terms to the left:
-3(5x+5)-(5(-3x+5))=0
We multiply parentheses
-15x-(5(-3x+5))-15=0
We calculate terms in parentheses: -(5(-3x+5)), so:
5(-3x+5)
We multiply parentheses
-15x+25
Back to the equation:
-(-15x+25)
We get rid of parentheses
-15x+15x-25-15=0
We add all the numbers together, and all the variables
-40!=0
There is no solution for this equation

See similar equations:

| x^2−12x+20=0 | | 3x-5x+7=x-5+12 | | x2−12x+20=0 | | 7/22(44)=2r | | 15=x÷5 | | 2d=3d−10 | | 16x+2=11x-3 | | x-11.66=0.2x | | -d/5-128-12=-4 | | 8x+240=0 | | x-10.20=0.2x | | 2x^2-9x-68=0 | | -56=4b | | 200-20m=500-50m | | x-8.75=0.2x | | -4+x=7(x-6 | | 8-2c=3c-2 | | 2/3t-4/6t=4-9 | | -16s+8=-8s | | n=12(3)^n-1 | | 180=5x+(x+54)+90 | | 4p+2=18.9= | | -12m+8-8=-11m-7 | | 5=8n/3-11 | | x+4x-1=21 | | -5x-21=4x3 | | -20=r/20 | | 398+200+24.25u=1,762 | | -8q+15=-10q-7 | | -3x=-5x-8 | | 7f=-364 | | 20-r=18 |

Equations solver categories